Importing the Plantation: The Greater Caribbean Trade and Loyalist Nova Scotia’s Public Revenue, 1789–1835 - Tillotson, Shirley (Journal of the Royal Nova Scotia Historical Society)

(untitled) (Royal Nova Scotia Historical Society, 2022)
Drawing on Halifax customs house reports, Tillotson reveals in broad terms the extent to which, between 1789 and 1835, the public revenue of the Province of Nova Scotia was drawn from taxes on imported goods that had been produced by the harshly exploited labour of enslaved people in the plantations of the greater Caribbean. With trade taxes generating two-thirds of the provincial revenue and the major customs port, Halifax, collecting between 38 percent and 73 percent of its trade taxes on slave-made goods, she argues that, in all of the areas where the Province spent on public goods, Nova Scotians benefitted substantially from a revenue that derived from the labour of enslaved people. One kind of benefit was the funding of economic infrastructure. The other was the payment of salaries to professional men who did government work. In the latter case, she shows, government work often had a social control element, one that reproduced in Nova Scotia the racialized hierarchy of the plantation world. The ideal of independent farming and fishing, one of the touchstones of settler economic life, counted for little against the commitment these professional men showed to the white supremacist culture that defended plantation society.